Cyber Bullying Pasukan Siber (Buzzer) Media Sosial Dalam Upaya Menjatuhkan Kredibilitas Koordinator Pusat Badan Eksekutif Mahasiswa Seluruh Indonesia - Ahmad, Zakly Hanafi; Syahrier, Fajar Alan; Anshori, M Wira; Muhammad, Hatta Abdi (Jurnal Administrasi Politik dan Sosial, 2025)
The use of social media, which initially was a means of socializing and sharing information, has now developed into a forum for conveying people's aspirations and opinions, including socio-political views. Political actors use social media for branding, campaigns and building public opinion. Cyber ​​troops or buzzers are actively involved in spreading issues, publishing politicians, and even criticizing the opposition. One example is cyber bullying against the Chair of BEM SI following the student demonstration on April 11 2022. This research aims to identify the form of cyber bullying against the Chair of BEM SI, the structure of the movements, and the language used by the buzzer. The method used is digital ethnography with primary data from virtual in-depth interviews and secondary data from big data on social media, online media and institutional data. The research results show that the buzzer succeeded in swaying public opinion by spreading negative news and provocative comments to damage the credibility of the Chair of BEM SI.